2013
DOI: 10.1177/0954405413510289
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding window for AA6061-T6 aluminium alloy

Abstract: In this study, friction stir welding window for AA6061-T6 aluminium alloy based on tool rotational speed and weld speed was developed. The formation of friction stir welding/processing zone has been analysed macroscopically and microscopically. Fracture locations of the joints were also analysed using scanning electron microscope. It has been experimentally found that the joint fabricated using tool rotational speed of 1000 r/min and weld speed of 40 mm/min (obtained from friction stir welding window), tool sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…FSW is considered as a solid-state process in which the base materials are placed next to each other and then a non-consumable tool comprising shoulder and pin is placed at the center of the joint line. 2527 Then, the joint is created due to heat generated by shoulder and stirring of plasticized materials by rotation of the tool pin with its traverse movement. 2830 A schematic view of the FSW process for dissimilar joint of Al alloys is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…FSW is considered as a solid-state process in which the base materials are placed next to each other and then a non-consumable tool comprising shoulder and pin is placed at the center of the joint line. 2527 Then, the joint is created due to heat generated by shoulder and stirring of plasticized materials by rotation of the tool pin with its traverse movement. 2830 A schematic view of the FSW process for dissimilar joint of Al alloys is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Existence of such smooth and regular river pattern has indicated mechanism of cleavage fracture. Some authors claimed that such micrographs indicating shear flow of material (striations) clearly infer to brittle failure [22].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that microstructure of the weld interface contributed to mechanical strength of the Weldment. Gadakh and Kumar [22] proposed a weldability window for FSW of AA6061-T6 alloy based on tool rotational speed and weld speed. Such weldability window provided a ready reckoner toward selecting suitable welding parameters to fabricate defect-free weldment.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome such drawbacks, friction stir welding (FSW), a solid-state welding technique, can be used. 710 In FSW, the blanks are joined by the action of a rotating tool with a pin getting in contact with the top surface of the sheets and then moving along the welding line with a proper tilt angle. The combined effect of tool rotation and translation involves heat generation by friction between tool and sheets, inducing a strong plastic deformation of the workpiece by promoting its complex mixing across the joint.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effect of tool rotation and translation involves heat generation by friction between tool and sheets, inducing a strong plastic deformation of the workpiece by promoting its complex mixing across the joint. 812 As a consequence, a plasticised region is created around the tool so that the material is extruded from the leading side (advancing side (AS)) to the trailing side (retreating side (RS)) of the weld. Kumar and Kailas 13 investigated the mechanism of weld formation and the role of FSW tool in such mechanism.…”
Section: Introductionmentioning
confidence: 99%